Geopolitikai változások a Balkánon - Hidvéghi, Balázs (Közép-Európai Közlemények, 2017)
The dissolution of Yugoslavia began as a civil war and it developed into a bloody and ruthless real war. Although the weak internal cohesion of the multi-ethnic state created after the First World War was somewhat strengthened by the firm hand of President Tito following its recreation in 1945, even his efforts failed to produce a common southern Slav national community. The very essence of the raison d’être of Yugoslavia disappeared with his death and the end of the Cold War, and the process of dissolution almost immediately began. The fact that it developed into a several year-long military conflict was the result of numerous reasons. Primarily it had a lot to do with the high number of ethnically mixed territories, and the radically different levels of development and different interests of the various member states within the Federation. The international and European community partly had no interest, partly had no means to hinder the escalation of the crisis. The dissolution of Yugoslavia illustrated in little the global political situation of the 1990s: a new geopolitical reality in which in the aftermath of the breakup of the Soviet Union, Russia was too weak to enforce its own political interests, the European Union continued to remain weak and divided in strategic questions, and this left the United States unhindered to act according to its own decisions and interest as the de facto only great power in the world.